Case report: Open replacement of incomplete semi-circular traumatic ruptures of the ascending and descending aorta. Issue 1 (December 2016) - Mytsyk, Miroslawa; Grapow, Martin; Shahinian, Jasmin; Maurer, Markus; Gurke, Lorenz; Eckstein, Friedrich
Abstract An incomplete traumatic rupture of the ascending aorta is a rare but life-threatening condition. Hence, the assessment of the extent of the injury prior to therapy is crucial. We report a case of a 50-year-old male with traumatic aortic rupture who underwent emergency surgery after the evaluation of computed tomography scan (CT-scan). The surgical treatment involved replacement of the ascending aorta and stent implantation in descending aorta due to its covered rupture.